2019
DOI: 10.1177/1558925019888816
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalysis and UV-blocking properties of cotton fabric functionalized with BiPO4nanorods

Abstract: Uniform monoclinite bismuth phosphate (BiPO4) nanorods were fixed on commonly used cotton fabric using two-dip–two-nip technique. Chitosan and acetic acid were applied to act as cross-linking agent in preparing the finishing solution. In this article, BiPO4 nanorods modified cotton fabrics for UV-blocking, as well as photocatalytic degradation of RhB has been studied. This coated fabric was characterized by X-ray diffraction, field-emission scanning electron microscopy equipped with energy-dispersive X-ray spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The POT cage coating imparted excellent UV-blocking performance (89% blocked at 350 nm), hydrophobicity (water contact angle > 148°) and antibacterial activity (Escherichia coli, Staphylococcus epidermidis, and Staphylococcus aureus bacteria) to cotton fabrics. Jin et al (2019) successfully prepared bismuth phosphate (BiPO4) nanorods coated cotton fabrics by two-dip-two-nip technique. Chitosan and acetic acid acted as cross-linking agents between BiPO4 and cotton fibers as seen in UV-VIS absorption and FTIR results.…”
Section: Inorganic Compounds Metal Nanoparticles Ldh Materials and Co...mentioning
confidence: 99%
“…The POT cage coating imparted excellent UV-blocking performance (89% blocked at 350 nm), hydrophobicity (water contact angle > 148°) and antibacterial activity (Escherichia coli, Staphylococcus epidermidis, and Staphylococcus aureus bacteria) to cotton fabrics. Jin et al (2019) successfully prepared bismuth phosphate (BiPO4) nanorods coated cotton fabrics by two-dip-two-nip technique. Chitosan and acetic acid acted as cross-linking agents between BiPO4 and cotton fibers as seen in UV-VIS absorption and FTIR results.…”
Section: Inorganic Compounds Metal Nanoparticles Ldh Materials and Co...mentioning
confidence: 99%
“…Our body gets protection from skin-related diseases by wearing sun-protective clothes made of nano ZnO. Jin et al 35 reported that the cotton fabric which protects UV rays is an important component of outdoor textiles. UV protection is discovered due to the nano ZnO bandgap of 3.37 eV and the ability to absorb light at 376 nm, 36 which is the wavelength range of ultraviolet rays.…”
Section: Introductionmentioning
confidence: 99%